2020
DOI: 10.1590/1516-4446-2019-0489
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype in bipolar disorder: an 18-month prospective study

Abstract: Objective: Circadian dysregulation plays an important role in the etiology of mood disorders. Evening chronotype is frequent in these patients. However, prospective studies about the influence of chronotype on mood symptoms have reached unclear conclusions in patients with bipolar disorder (BD). The objective of this study was to investigate relationship between chronotype and prognostic factors for BD. Methods: At the baseline, 80 euthymic BD patients answered a demographic questionnaire and clinical scales t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
9
1
3
Order By: Relevance
“…Our results suggest that late chronotype predominantly increases the risk for a depressive mood course rather than a hypomania/mania mood course. One previous study also reported that late chronotypes had more anxiety symptoms during follow up (Melo et al 2020), but this effect was not detected in the current study possibly due to the smaller number of GAD-7 assessments. Both previous studies only included individuals who were euthymic at baseline, whereas in the current study all participants were included and baseline mood was adjusted for in the analyses.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Our results suggest that late chronotype predominantly increases the risk for a depressive mood course rather than a hypomania/mania mood course. One previous study also reported that late chronotypes had more anxiety symptoms during follow up (Melo et al 2020), but this effect was not detected in the current study possibly due to the smaller number of GAD-7 assessments. Both previous studies only included individuals who were euthymic at baseline, whereas in the current study all participants were included and baseline mood was adjusted for in the analyses.…”
Section: Discussioncontrasting
confidence: 92%
“…While higher doses of melatonin taken at bedtime have been tested in people with bipolar disorder as a sleep aid (Baandrup et al 2011) and to improve cardiometabolic health (Mostafavi et al 2017), it remains to be determined if melatonin, when used to phase advance circadian timing, can improve mood course in people with bipolar disorder. While the five years of follow up in this study is meaningfully longer than the previous studies (Takaesu et al 2017;Melo et al 2020), the granularity and frequency of the data collection nonetheless remains modest. The gathering of self-reported mood symptoms every two months and an in-person clinical assessment every two years may still have not accurately captured the nuanced daily to weekly variability in mood in people with bipolar disorder.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations